Mortality of Dysmicoccus neobrevipes Beardsley and Mangosteen Shelf Life (Garcinia mangostana L.) Consequences of Applying Patchouli Essential Oil Concentration (Pogostemon cablin Benth) at the Maturity Level of Mangosteen in the Laboratory - Maman, Maman; Amalia, Lia; Mulia, Agus Surya (Journal of Innovation and Research in Agriculture, 2024)
Mangosteen is a flagship fruit as a potential export commodity with high economic value. The export activities of Indonesian mangosteen are limited due to constraints of plant pest organisms (OPTK) and the quality of mangosteen fruit. The use of patchouli essential oil can be an environmentally friendly alternative control method that does not leave residues and can maintain the quality of mangosteen fruit. The purpose of this research is to identify the type of mealybugs that attack mangosteen fruit and the effect of patchouli essential oil on the mortality of mealybugs and the shelf life of mangosteen (color, weight loss, and firmness). The research was conducted at the Entomology Laboratory of Animal, Fish, and Plant Quarantine, West Java, from January to April 2024. The method used was an experimental method with a Split Plot Completely Randomized Design. Mortality and shelf life testing was conducted with 16 treatments, namely n0k1, n0k2, n0k3, n0k4, n1k1, n1k2, n1k3, n1k4, n2k1, n2k2, n2k3, n2k4, n3k1, n3k2, n3k3, and n3k4 (n= concentration of patchouli oil 10 ml/L; 20 ml/L; and 30 ml/L; k= fruit maturity level 3, 4, 5, and 6), each repeated twice. The results showed that the mealybug that attacks mangosteen fruit and was the subject of the study is Dysmicoccus neobrevipes. The use of patchouli essential oil at a test concentration of 30 ml/L could increase the mortality of Dysmicoccus neobrevipes at all levels of mangosteen fruit maturity. This concentration caused 100% mortality of Dysmicoccus neobrevipes at maturity level six 72 hours after treatment. The 30 ml/L concentration of essential oil also maintained the shelf life of mangosteen fruit, resulting in low color change values (0.24-0.35), low weight loss (50.35-61.91 g), and low fruit firmness levels (34.50-43.15 kg.s/mm).